Implementasi Quadruple Helix Dalam Mendorong Pertumbuhan Ekonomi Kreatif - Ivana Oktarina Sopacua; Noormalita Primandaru (Akademi Akuntansi YKPN Yogyakarta, 2020)
The Quadruple Helix concept is the development of Triple Helix by integrating civil society. The Quadruple Helix approach is far from being considered a definite and established concept in research and innovation policy. The purpose of this study is to describe the Quadruple Helix application which can be used as a system framework to increase creative economic growth as a tourism attraction in the city of Yogyakarta. The method used in this research is descriptive qualitative, primary data obtained from observations, interviews, and FGDs with representatives from academia, fashion creative economy actors, communities, and the government. The location of this research is the Ngasem Market and Malioboro areas. The results of this research are skills development training that focuses only on certain groups such as designer groups, pencorek groups or other groups, so that training participants can learn according to their interests and talents, hold batik fashion exhibitions near tourist objects that are visited by many tourists, and marketing strategy training that is oriented to the environment and changes in consumer behavior.